TPM, proposta de implantação do pilar manutenção autônoma, no setor da armação em uma empresa montadora de automóveis - Dunetz, Edilson (2014)
To achieve its objectives, the TPM (Total Productive Maintenance), strategy needs to be developed organizational skills management and control, as well as new operators and assignments manutentores. These changes add new attitudes towards work, seeking improvements in the structure of production and maintenance system in human and material terms. The goal of TPM is the overall operating efficiency of the equipment and its maximum production. We present a theoretical framework emphasizing the TPM pillars Autonomous Maintenance and Education & Training. The objective of this work is the implementation of the Autonomous Maintenance Pillar Frame sector industries in the automotive section. First there were the difficulties encountered during the implementation of Pillar AM, be they cultural or organizational, such as lack of training and control indicators. A general planning was done by creating a registry of TPM , stating in detail their responsibilities , also emphasized the need for training for all employees , through an implementation schedule and audits confirm that the knowledge acquired by employees and also consolidate ( seven) steps of the AM.